Market Behaviour and Economic Analysis of Arrivals and Prices of Potato in Fruit and Vegetable Market Okara (Punjab), Pakistan - Hafiz Saqib Habib; Nasir Mahmood (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
The present study was conducted to analyze the behaviour of arrivals and wholesale price of potatoes in the Fruit and Vegetable (F and V) Market of Okara City, Pakistan. Time series data for the last seven years was collected on market arrivals and prices of potatoes from the government department. The Compound Annual Growth Rate (CAGR) was found to be positive (30%) regarding prices, and negative (-7%) for arrivals of potatoes. The variation in prices and arrivals differed across the months. The findings revealed that the highest (211.3%) arrivals variation occurred during the month of November, and the highest (25.89%) price variation took place during the month of February. The results of the Cuddy-Della-Valle Index showed medium instability (24.38 %) in case of prices, and low instability (4.76%) regarding the arrivals. The Karl Pearson Correlation Coefficient method indicated that mostly across the months, there exists a positive relationship between market arrivals and prices of potatoes with the exception of a few months. The study confirmed the highest seasonal arrivals index (338.11%) for the month of February and the highest seasonal price index (136.98%) for the month of November. In order to get maximum benefit from marketing of potatoes, it is suggested that all the concerned stakeholders should look timely and properly at the trend of market prices and market arrivals of potatoes in the F & V markets. Proper management along with market intelligence of arrivals and prices would increase the welfare of farmers, consumers and other stakeholders which involved in the agri-food supply chain of potato.